Hubungan Premenstruasi Syndrome Dengan Disminore Pada Siswi SMAN 2 Bangkinang Kota - Lestari, Nanda; Hidayat, Ridha; Ningsih, Neneng Fitria (El-Emir Institute, 2025)
Dysmenorrhea is one of the disturbances experienced by women during their menstrual period. One of the causes of dysmenorrhea can be due to premenstrual syndrome (PMS), which includes both internal and external stressors affecting women. Stress among female students is often caused by pressure before exams, school assignments, graduation plans, and personal problems. This study aims to determine the relationship between premenstrual stress and dysmenorrhea among students at SMAN 2 Bangkinang Kota. The research employed a descriptive correlational survey design with a cross-sectional approach. The population consisted of 675 female students from grades X to XII. The sample was determined using the Slovin formula, with stratified random sampling and purposive sampling techniques, resulting in a total of 87 students. Data were collected using the Shortened Premenstrual Assessment Form (SPAF) questionnaire. The data were analyzed using the chi-square test with the Fisher exact test for significance. The results showed that 77 students (88.5%) experienced premenstrual syndrome, and 75 students (86.2%) experienced dysmenorrhea. Bivariate analysis revealed that of the 77 students with premenstrual syndrome, 70 (90.1%) experienced dysmenorrhea, while 7 (9.1%) did not, due to other factors. Further studies are recommended to conduct quasi-experiments to observe whether there are differences in women who experience stress compared to those who do not.